2012
DOI: 10.1007/s10072-012-1044-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of frovatriptan versus other triptans in the acute treatment of menstrual migraine: pooled analysis of three double-blind, randomized, crossover, multicenter studies

Abstract: The objective of this study was to review the efficacy and safety of frovatriptan (F) versus rizatriptan (R), zolmitriptan (Z) and almotriptan (A), in women with menstrually related migraine (IHS criteria) through a pooled analysis of three individual studies. Subjects with a history of migraine with or without aura were randomized to F 2.5 mg or R 10 mg (study 1), F or Z 2.5 mg (study 2), and F or A 12.5 mg (study 3). The studies had an identical multicenter, randomized, double-blind, crossover design. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 19 publications
2
26
0
2
Order By: Relevance
“…An additional interesting finding of our retrospective analysis is that immediate and delayed efficacy of frovatriptan in the subgroup of OCMM is superimposable to that previously observed in the whole subgroup of women with menstrual migraine [6]. …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…An additional interesting finding of our retrospective analysis is that immediate and delayed efficacy of frovatriptan in the subgroup of OCMM is superimposable to that previously observed in the whole subgroup of women with menstrual migraine [6]. …”
Section: Discussionsupporting
confidence: 55%
“…As shown in numerous randomized trials, frovatriptan represents a well known and effective option for acute [46, 11] or prophylactic treatment [1517] of menstrual migraine. The present study, based on a pooled analysis of three double-blind, randomized, direct comparative, cross-over studies [1214], demonstrates that frovatriptan is clinically effective also for the acute treatment of OCMM, a particular menstrual migraine subtype.…”
Section: Discussionmentioning
confidence: 99%
“…What is particularly significant is the number of women who were already reporting a pain-free state at 4 h (64 %) and even more remarkably at 24 h (76 %). Comparative studies of other triptans were used for treating, an acute attack of MRM showed that frovatriptan is highly effective when used alone it produced a pain-free state in 52 % of the patients at 4 h, and in 66 % of the patients at 24 h [15]. Therefore, if the above result is compared with the percentages of frovatriptan’s effectiveness obtained in the present trial, it becomes quite clear that added benefit can be derived from combining dexketoprofen with frovatriptan rather than using frovatriptan alone.…”
Section: Discussionmentioning
confidence: 99%
“…In the pooled analysis of the three direct comparative studies of frovatriptan versus other triptans, a total of 18 drug-related adverse events were recorded in 401 menstrually related attacks treated [Allais et al 2012]. No statistically significant differences were observed in the rate of attacks associated with drug-related adverse events between frovatriptan (5%) and the comparators (4%).…”
Section: Safety Of Frovatriptan In MMmentioning
confidence: 99%
“…Previous medications were rated at baseline as good or very good for effectiveness by only 20% of menstrual migraineurs and 19% of nonmenstrual migraineurs, while the Table 4. Demographic and clinical characteristics and main efficacy parameters for the whole population of three randomized controlled studies comparing frovatriptan with rizatriptan, zolmitriptan, or almotriptan, and for the subgroup of women with menstrually related migraine (Allais et al [2012]; Cortelli et al [2011] …”
Section: Efficacy Of Frovatriptan In Mm: Evidence From Open-label Stumentioning
confidence: 99%